Development of a systems dynamics model to support the evolution of a collection of legacy systems into an enterprise with an integrated set of capabilities - Terry, Sian A., author; Chandrasekar, V., advisor; Simske, Steve, committee member; Shahroudi, Kamran Eftekhari, committee member; Cheney, Margaret, committee member; Meeks, William, committee member (Colorado State University. Libraries, 2025)
As development of systems shift from the periodic addition of key features toward the continual sustainment of the system of interest through an everchanging environment, novel systems engineering tools will need to be developed to meet the growing needs of the stakeholders. Achieving this goal may necessitate the evolution of legacy systems into an enterprise system. This dissertation details the steps needed to create such a tool, known as the Enterprise Lifecycle Model; a novel framework that uses systems dynamics to define a holistic and reductive model depicting the connections between various key components of the system of interest. As well as how this model will support a common vision. This model will be validated to ensure it can be effectively used on various aerospace ground systems and support legacy system evolution into an enterprise system.
Keywords: program management; system dynamics; systems thinking; system development; enterprise lifecycle model; systems engineering